Acrosin Activity in Cryopreserved Human Spermatozoa - Dunayevskaya, A. V.; Chub, N. N.; Kramar, M. I.; Rodionova, V. L. (Problems of Cryobiology and Cryomedicine, 2003)
There have been presented the results of the analysis of Â various freezing rates effect on morphological integrity and enzymic activity of human spermatozoa. It has been shown that during freezing with the program and with the rate of 2500Â°C/min the acrosin activity and structural integrity of spermatozoa are kept.